Can boards of directors in large companies effectively prevent fraud? - Meiliana; Nelson Ng; Sheila Septiany (Jurnal Akademi Akuntansi, 2024)
ABSTRACT Purpose: The aim to test the impact of the characteristics of board of directors in reducing and preventing the possibility of financial statement fraud with firm size as variable moderating. Methodoly/Approach: The technique used purposive sampling method resulting of total 435 data and 87 companies in mining sector for the period 2018 – 2022. Findings: The result of this study is that firm size do not strengthen the board independence, board remuneration, board financial and industry expertise, and number meeting board of director on fraudulent financial statement. However, firm size strengthens the CEO financial and industry expertise on fraudulent financial statement. Another result is CEO financial and industry expertise, board financial expertise has a negative influence on fraudulent financial statement, but board independence, board remuneration, board industry expertise and board effort do not have influence on fraudulent financial statement. Practical and Theoretical contribution/Originality: This research is expected to be helpful to the companies regarding the importance of the characteristics of the board of directors whether in large and small companies to prevent and detect fraudulent financial statements. Research Limitation: This limitation is focused only on mining sector companies, and it only measures the characteristic board of directors’ variables.